Inheritance of resistance to leaf rust in bread wheat cultivars HUW 510, HW 2044, K 9644 and PBW 443 - and RAM CHARAN, S. BHARATHIDASAN, P. BAHADUR (Indian Phytopathology, 2006)
The study of inheritance of resistance to three pathotypes viz., 0R9 (106), 29R23 (104B) and 109R31-1 (77-2) of Puccinia triticina was carried out in four popular bread wheat cultivars viz., HUW 510, HW 2044, K 9644 and PBW 443. All the cultivars showed resistance to above leaf rust pathotypes. Analysis of F2 seedlings revealed that in K 9644 one dominant resistance gene against pathotypes 109R33-1 (77-2), 29R23 (104B) and two dominant independent resistance genes against 0R9 (106) were responsible for governing the resistance. In PBW 443 and HUW 510, the resistance was controlled by two dominant independent genes to all the three selected pathotypes. In HW 2044, one dominant resistance gene to 109R31-1 (77-2) and 2 dominant independent resistance genes each to 29R23 (104B) and 0R9 (106) provided resistance. In diallel crosses, F1 seedlings were resistant indicating the dominant nature of resistance. F2 seedlings of crosses K 9644 X PBW 443, HW 2044 X PBW 443 and HW 2044 x K 9644 did not segregate for susceptibility against pathotype 0R9 (106) indicating that at least one resistance gene/s was similar among the two cultivars. The seedlings of the crosses HW 2044 X HUW 510 and HUW 510 X PBW 443 showed quadragenic resistance. The allelic test is done on the four test cultivars crossed with isogenic Lr lines tested with 0R9(106) and from the segregation pattern, four genes viz., Lr1, Lr13 and Lr23 have been confirmed in these cultivars.